2022
DOI: 10.28991/cej-2022-08-09-01
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flood Discharge due to Impact of Tropical Cyclone

Abstract: Tropical Cyclone Seroja, which occurred between April 2 to 6, 2021, is one of the strongest storms ever in East Nusa Tenggara. The track results of the cyclone showed that Seroja, formed at coordinates 10.5° S and 123° E, moved towards west longitude to Sumba Island and continued towards Australia. Moreover, the Global Precipitation Measurement (GPM) output was used to analyze the rainfall conditions at the center of the Seroja cyclone through the Kambaniru watershed in East Sumba, and the results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The movement of TC Seroja's center from its beginning to its end can be seen in Figure 1. Other research found that TC Seroja influenced the intensity of extreme rainfall and wind speed in Nusa Tenggara Timur and western Australia [13], [14]. This extreme rainfall triggered flooding in several areas [15], [16].…”
Section: Introductionmentioning
confidence: 92%
“…The movement of TC Seroja's center from its beginning to its end can be seen in Figure 1. Other research found that TC Seroja influenced the intensity of extreme rainfall and wind speed in Nusa Tenggara Timur and western Australia [13], [14]. This extreme rainfall triggered flooding in several areas [15], [16].…”
Section: Introductionmentioning
confidence: 92%
“…Water resources management and related risks are increasingly becoming an important concern of contemporary society (Ebodé et Ebodé et al, 2024c). Among the wide range of existing hydrological risks, ooding appears to be one of the most devastating, considering the enormous damage it often causes (Samanta et al, 2018;Krisnayanti et al 2022;Ekwueme, 2022;Manzoor et al, 2022). Between the 1990s and 2010s, oods caused the deaths of more than 158,000 people around the world (CRED, 2018).…”
Section: Introductionmentioning
confidence: 99%